Knowledge, Attitude, and Perception of African Optometrists on Fellowship of the American Academy of Optometry (AAO): A Cross-Sectional Survey - Ovenseri-Ogbomo G; Richter SM; Ekpenyong BN; Ocansey S; Ebri AE; Akuffo KO; Osuagwu UL (Clinical Optometry)
Godwin Ovenseri-Ogbomo,1 Susarah Maria Richter,2 Bernadine N Ekpenyong,3 Stephen Ocansey,4 Anne Effiom Ebri,3 Kwadwo O Akuffo,5 Uchechukwu L Osuagwu6,7 1Department of Optometry, Centre for Rural Health Sciences, University of the Highlands and Islands, Inverness, UK; 2Department of Optometry, Faculty of Health Sciences, University of Johannesburg, Johannesburg, South Africa; 3Department of Public Health, College of Medical Sciences, University of Calabar, Calabar, Nigeria; 4School of Optometry and Vision Sciences, School of Allied Health Sciences, College of Health and Allied Sciences, University of Cape Coast, Cape Coast, Ghana; 5Department of Optometry and Visual Science, College of Science, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana; 6School of Medicine, Bathurst Rural Clinical School, Western Sydney University, Bathurst, New South Wales, Australia; 7African Vision Research Institute, Discipline of Optometry, University of Kwazulu-Natal, Durban, South AfricaCorrespondence: Uchechukwu L Osuagwu, Senior Lecturer and Academic Lead, Rural Health, School of Medicine, Bathurst Rural Clinical School, Western Sydney University, PO Box 9008, Bathurst, NSW, 2795, Australia, Tel +61 2 9685 9903 ; +61 401193234, Email l.osuagwu@westernsydney.edu.auIntroduction: Following the formal launch of the AAO-African Chapter in October 2023, there was a renewed interest among African Optometrists to obtain the Fellowship of the American Academy of Optometry (FAAO). This paper investigates the awareness of the FAAO process among African optometrists and their perception of the newly established African Chapter’s role in advancing the profession on the continent. The survey addresses a critical gap in understanding and highlights the pivotal role the African Chapter can play in advancing the optometry profession on the continent, contributing valuable insights for shaping strategies to enhance awareness, promote professional development, and foster a sense of belonging among African optometrists within the global optometry community.Methods: A self-administered web-based cross-sectional survey was conducted from October 25 to 30, 2023, targeting African Optometrists who had joined the candidate for AAO WhatsApp group, created by the African Chapter. The survey aimed to collect data on the participants’ knowledge, perceptions, and attitudes toward the FAAO process and the newly established African Chapter.Results: The majority of the 302 African optometrists that participated in the survey, were under 40 years old and predominantly from Nigeria or Ghana. Despite a high intention to apply for the FAAO (77.2%), a significant proportion (82.1%) were unaware of the process. Nevertheless, nearly half of the respondents perceived benefits from the fellowship with regard to enhancing professional development and status. While one-third of respondents were aware of the African Chapter before joining, nearly all expressed a desire to become official members.Conclusion: The critical gap in awareness regarding the FAAO process among African optometrists suggests the need for targeted strategies to increase awareness, promote professional development, and foster a sense of belonging among African optometrists within the global optometry community.Keywords: education, optometry, awareness, professional development, equity